MANAJEMEN KURIKULUM PENDIDIKAN INKLUSIF - Mukhtar Mukhtar (Al-Rabwah, 2019)
This research is a field research (field reseach) using a naturalistic research approach that aims to determine the management of planning, organizing, implementing and evaluating an inclusive education curriculum. Sources of data in this study are the Principal, Waka Curriculum, Subject Teachers and Counseling Guidance Teachers. Data collection techniques using observation, interviews and documentation. The data validity technique uses data triangulation and data analysis techniques use the Mills and Huberman models. The results showed that curriculum planning used a grass roots approach, which involved all stakeholders in SMPN 1 Sangatta Utara. Organizing the curriculum using the Integrated Curriculum approach, arranging and modifying subjects in an integrated manner. The curriculum implementation uses the TORI model approach, directing students more towards aspects of social change and the teaching system adjusting the needs of special needs students. Curriculum evaluation uses the Educational System Evaluation approach, including inputs (materials, plans, tools), processes and results achieved in a broader sense.